Masserepræsentation - Borch, Christian (K&K - Kultur og Klasse, 2014)
Stefan Jonsson, Crowds and Democracy: The Idea and Image of the Masses from Revolution to Fascism. New York & London: Columbia University Press, 2013, 321 sider